Mechanistic in vitro studies indicate that the clinical drug–drug interactions between protease inhibitors and rosuvastatin are driven by inhibition of intestinal BCRP and hepatic OATP1B1 with minimal contribution from OATP1B3, NTCP and OAT3. Issue 2 (22nd February 2023) - Elsby, Robert; Coghlan, Hannah; Edgerton, Jacob; Hodgson, David; Outteridge, Samuel; Atkinson, Hayley
Abstract: Previous use of a mechanistic static model to accurately quantify the increased rosuvastatin exposure due to drug–drug interaction (DDI) with coadministered atazanavir underpredicted the magnitude of area under the plasma concentration–time curve ratio (AUCR) based on inhibition of breast cancer resistance protein (BCRP) and organic anion transporting polypeptide (OATP) 1B1. To reconcile the disconnect between predicted and clinical AUCR, atazanavir and other protease inhibitors (darunavir, lopinavir and ritonavir) were evaluated as inhibitors of BCRP, OATP1B1, OATP1B3, sodium taurocholate cotransporting polypeptide (NTCP) and organic anion transporter (OAT) 3. None of the drugs inhibited OAT3, nor did darunavir and ritonavir inhibit OATP1B3 or NTCP. All drugs inhibited BCRP‐mediated estrone 3‐sulfate transport or OATP1B1‐mediated estradiol 17β‐D‐glucuronide transport with the same rank order of inhibitory potency (lopinavir>ritonavir>atazanavir>>darunavir) and mean IC50 values ranging from 15.5 ± 2.80 μM to 143 ± 14.7 μM or 0.220 ± 0.0655 μM to 9.53 ± 2.50 μM, respectively. Atazanavir and lopinavir also inhibited OATP1B3‐ or NTCP‐mediated transport with a mean IC50 of 1.86 ± 0.500 μM or 65.6 ± 10.7 μM and 5.04 ± 0.0950 μM or 20.3 ± 2.13 μM, respectively. Following integration of a combined hepatic transport component into the previous mechanistic static model using the in vitro inhibitory kinetic parameters determined above for atazanavir, the newly predicted rosuvastatin AUCR reconciled with the clinically observed AUCR confirming additional minor involvement of OATP1B3 and NTCP inhibition in its DDI. The predictions for the other protease inhibitors confirmed inhibition of intestinal BCRP and hepatic OATP1B1 as the principal pathways involved in their clinical DDI with rosuvastatin. Abstract : This work sought to clarify the mechanisms underlying clinical DDIs between rosuvastatin and protease inhibitors. Investigating in vitro inhibition of the critical transporter disposition pathways of rosuvastatin, and subsequent incorporation of cell test system derived determined Ki values into mechanistic static equations, enabled successful quantitative prediction of clinical AUCRs. Predictions suggest the mechanisms driving DDI are principally inhibition of intestinal BCRP and hepatic OATP1B1, with minimal contribution from OATP1B3, NTCP or OAT3.